Kepuasan Kerja Karyawan Bagian Produksi CV. Wac Melalui Lingkungan Kerja Fisik dan Motivasi Kerja - Rahayu, Ganita Dimas Dwi; Mulyana, Aam Rachmat (Universitas Batanghari, 2024)
This study aims to determine the effect of physical work environment (variable X1) and work motivation (variable X2) on employee job satisfaction. The method used in quantitative method research uses descriptive data analysis methods and associative methods, the measurement scale used for data measurement is semantic differential, multiple regression analysis to measure the consistency of partial and simultaneous test values to test the hypothesis. This study shows the results partially that the physical work environment has a positive effect on employee job satisfaction and work motivation has a positive effect on employee job satisfaction, while simultaneously the physical work environment and work motivation affect job satisfaction. With a good physical work environment and the higher the motivation of employees at work, the better job satisfaction they have.